Lipoprotein Lipase is an Important Modulator of Lipid Uptake and Storage in Hypothalamic Neurons - Libby, Andrew E. (Biochem Biophys Res Commun, 2015)
LPL is the rate-limiting enzyme for uptake of TG-derived FFA in peripheral tissues, and the enzyme is expressed in the brain and CNS. We previously created a mouse which lacks neuronal LPL. This animal becomes obese on a standard chow, and we observed reduced lipid uptake in the hypothalamus at 3 months preceding obesity. In our present study, we replicated the animal phenotype in an immortalized mouse hypothalamic cell line (N41) to examine how LPL affects expression of AgRP as well as entry and storage of lipids into neurons. We show that LPL is able to modulate levels of the orexigenic peptide AgRP. LPL also exerts effects on lipid uptake into culture neurons, and that uptake of neutral lipid can be enhanced even by mutant LPL lacking catalytic activity. N41 cells also accumulate neutral lipid in droplets, and this is at least in part regulated by LPL. These data in addition to those published in mice with neuron-specific deletion of LPL suggest that neuronal LPL is an important regulator of lipid homeostasis in neurons and that alterations in LPL levels may have important effects on systemic metabolism and neuronal lipid biology.